Inhibitory control and traumatic brain injury: The association between executive control processes and social communication deficits - Pearce, B.; Cartwright, Jade; Cocks, Naomi; Whitworth, Anne (Informa UK Limited, 2016)
© 2016 Taylor & Francis Group, LLC.Primary objective: To further examine the proposed relationship between executive impairments in inhibitory control and social communication difficulties reflecting poor inhibition following TBI. Method: Inhibitory control was assessed in 14 adults with TBI on the Hayling Sentence Completion Test (HSCT). Errors on Part B (failed inhibition) and Part B-Part A response latencies (delayed inhibition) were examined. A relative, friend or frequent communication partner of each participant with TBI completed the La Trobe Communication Questionnaire (LCQ) on the communication difficulties of the person with TBI. The Inhibitory Control Factor (ICF) score of the LCQ based on seven items relating to poor inhibition was specifically analysed against performance on the HSCT. Results: Multiple regression analysis indicated that 58% (51% adjusted) of the variance in LCQ ICF scores was accounted for by measures on the HSCT. Only B–A response latencies on the HSCT explained a significant proportion of the variability in LCQ ICF scores. Conclusions: Reduced inhibition speed may more strongly contribute to disinhibited communication behaviours than failures in inhibition. These findings contribute to understanding of the cognitive processes underlying social communication and have the potential to support and inform the use and development of management practices for individuals following TBI.